Analisis Bagi Hasil Pembiayaan Pasca Covid-19 Terhadap Permintaan Pembiayaan di PT. BPRS Haji Miskin Kabupaten Tanah Datar - Sabri; nasfi, nasfi (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2021)
Research at PT. BPRS Haji Miskin Tanah Datar Regency from May to July 2021, the purpose of the study was to see the effect of profit sharing during the COVID-19 period on the demand for financing at PT. BPRS Haji Miskin. Covid-19 started in Indonesia in December 2019 and still hasn't ended until August 2021 now, so the data taken is semester data, for 5 (five) semesters starting from June 2019 to June 2021. Research Methods with quantitative and qualitative methods and analyzing data with analysis simple regression and correlation. For data processing using SPSS. The results of the regression coefficient research with negative results, reflecting that the level of financing profit sharing is increased by one unit, the demand for financing (credit) will decrease by 0.5759 rupiah or, while from the value of r = 0.825, where if the value of r is close to 1, then there is a relationship positive and strong linear If it is assumed that all other variables are considered constant. Shows a negative relationship between the level of profit sharing on the demand for financing at PT. BPRS Haji Miskin, this shows the inverse effect that lowering the rate of profit sharing will increase the demand for financing or vice versa.